2020
DOI: 10.1101/2020.06.23.167478
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recalcitrance ofCannabis sativatode novoregeneration; a multi-genotype replication study

Abstract: Full title (250 characters max):Recalcitrance of Cannabis sativa to de novo regeneration; a multi-genotype replication study Short title (100 characters max):Recalcitrance of Cannabis sativa to de novo regeneration methods Abstract 2Cannabis sativa is relatively recalcitrant to regeneration from somatic tissues, but several 3 reports have been published demonstrating a response. Most reports show low levels of 4 regeneration from somatic tissues, but a landmark publication by Lata et al. in 2010 reported 5 reg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…While Page et al [77] demonstrated that DKW was more suitable for Stage 2 micropropagation of Cannabis, their findings likely represent an underestimate of the benefits as the study was conducted for only one subculture of Stage 2 plants, while the issues of culture decline generally increase over multiple subcultures. Using DKW based media, several cultivars of Cannabis have now been maintained for multiple years with no obvious signs of decline [89]. Despite the improvement over MS based media, some signs of nutrient deficiency were still observed, and further improvements are likely possible through optimization of basal media.…”
Section: Shoot Regenerationmentioning
confidence: 99%
See 4 more Smart Citations
“…While Page et al [77] demonstrated that DKW was more suitable for Stage 2 micropropagation of Cannabis, their findings likely represent an underestimate of the benefits as the study was conducted for only one subculture of Stage 2 plants, while the issues of culture decline generally increase over multiple subcultures. Using DKW based media, several cultivars of Cannabis have now been maintained for multiple years with no obvious signs of decline [89]. Despite the improvement over MS based media, some signs of nutrient deficiency were still observed, and further improvements are likely possible through optimization of basal media.…”
Section: Shoot Regenerationmentioning
confidence: 99%
“…Earlier reviews on the state of C. sativa micropropagation and regeneration largely failed to underscore the many challenges in the existing body of research. These challenges include incomplete and ambiguously reported results [28,67,74,81,82,84,86], recalcitrance to regeneration [28,68,81,82,86,88]; genotype and tissue-specific responses to regeneration [68,81,82,87,88]; and a lack of reproducibility of successful protocols in the literature [77,89].…”
Section: Regeneration In C Sativamentioning
confidence: 99%
See 3 more Smart Citations